HAEMATOLOGICAL AND SERUM BIOCHEMICAL INDICES OF BROILER CHICKEN FED VARYING LEVELS OF RICE OFFAL AS SUBSTITUTE FOR WHEAT OFFAL BASED DIETS - Haruna, I. M.; Bello, K. M.; Doma, U. D.; Egbo, M. L.; Jamaa, N.A.; Ambore, C.B.; Apeh, D.; Gukut, M. Y.; Rukayya, Y. L. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
An eight-week study was conducted on 300 broiler chickens to assess the effects of replacing wheat offal with rice offal on their haematological and serum biochemical parameters. Four diets were formulated with rice offal replacing wheat offal at 0, 33.33, 66.67, and 100%. Birds were fed ad libitum, and blood samples were analysed at the end of the trial. Results showed that increasing rice offal levels significantly (p < 0.01) affected mean corpuscular haemoglobin (MCH), with higher value at 66.67% inclusion (71.20 pg). Other blood parameters pack cell volume (PCV), haemoglobin (Hb), red blood cell (RBC), white blood cell (WBC), mean Corpuscular haemoglobin concentration (MCHC), mean Corpuscular volume (MCV), and leukocyte counts) showed no significant differences. Serum biochemical analysis revealed a significant increase (P < 0.001) in urea levels at higher rice offal inclusion (7.80 mmol/l at 66.67% and 7.75 mmol/l at 100%), though still within normal ranges. Other parameters such as glucose (umo/l), albumin (g/dl), bilirubin (umol/l), total protein (g/dl), and cholesterol (mmol/l) remained unaffected. Overall, rice offal can be used as a complete substitute for wheat offal in broiler diets without health risks. However, kidney function and immune response should be monitored at higher inclusion levels. Additionally, dietary components like fibre or omega-3s should be considered to regulate lipid metabolism. Regular monitoring of kidney function, platelet count, and immune response are recommended, particularly at higher inclusion levels.